Perancangan Sistem Informasi Layanan Pengaduan Masyarkat dan Pengajuan Hibah Berbasis Web Dibagian Kesejahtraan Rakyat Kabupaten Situbondo - Moh. Dafid Halid; Achmad Baijuri (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The development of information technology plays an important role in improving the quality of public services, including the processes of public complaints and grant submissions. Currently, these services at the Welfare Section of Situbondo Regency are still carried out manually, which often causes recurring problems such as delayed verification, lack of transparency in decision-making, and difficulties in data archiving and retrieval. These challenges not only slow down administrative processes but also reduce public trust in government services. Therefore, the design of a web-based information system is considered crucial to support the implementation of e-government and to ensure more effective, efficient, and accountable services. This study aims to design an integrated web-based information system that facilitates both public complaints and grant submissions within one platform. The research method applied is Object Oriented Analysis and Design (OOAD), which emphasizes systematic analysis and modeling using the Unified Modeling Language (UML). The analysis phase includes identifying system requirements, business process modeling, and defining functional and non-functional needs. The design phase produces various models such as business process design, input-output forms, application architecture using a three-tier structure, UML diagrams (use case, activity, class, and sequence diagrams), and database modeling. The results of this research are expected to provide a system design that improves the speed of service delivery, enhances transparency through real-time status tracking, reduces the risk of data loss by implementing digital archiving, and increases efficiency in the verification process. Overall, the proposed system design contributes to strengthening good governance practices in Situbondo Regency and serves as a reference for similar developments in other local government institutions.